(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the stages and types of involvement and organization of extracurricular activities of students studying in the Ministry of Higher and Secondary Education of our country, as well as the duties and obligations of the employee who is in charge of this work are briefly described.